2013
DOI: 10.1021/ef3020052
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Vanadium/Nickel Proportionality in the Asphaltene Fraction of Crude Oil Using Thin-Layer Chromatography with Femtosecond Laser Ablation–Inductively Coupled Plasma–Mass Spectrometry

Abstract: A method that integrated thin-layer chromatography (TLC) with femtosecond laser ablation−inductively coupled plasma−mass spectrometry (fs-LA−ICP−MS) was developed for the determination of the proportionality of vanadium/nickel in the asphaltene fraction of crude oils. TLC is easy and fast to implement for separation of crude oil components requiring minimal amount of solvents, and fs-LA−ICP−MS allows for direct analysis of the TLC plates without any additional sample preparation. This method was tested on Vene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
36
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 32 publications
0
36
0
1
Order By: Relevance
“…Metals, particularly Ni and V, which can be present in crude oils at concentrations up to thousands of partspermillion, are predominantly associated (∼80%) with the asphaltene fraction of crude oils [1]. The presence of heavy metals in crude oils as free metals and/or associated oxide metals or complexed to organic compounds has been described in the literature.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Metals, particularly Ni and V, which can be present in crude oils at concentrations up to thousands of partspermillion, are predominantly associated (∼80%) with the asphaltene fraction of crude oils [1]. The presence of heavy metals in crude oils as free metals and/or associated oxide metals or complexed to organic compounds has been described in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…The result shown that proposed separation methodology allows to extract an important percentage of the V and Ni associated with asphaltenes [1,2]., Standard solutions of Ni and V=OTPPs in THF were used to collect the absorbance spectra. The Soret band characteristic of these compounds was observed at 412 and 420 nm, respectively, as shown in complementary Figure A.…”
mentioning
confidence: 99%
“…Most of the compounds trapped in crude oils correspond to vanadium and nickel complex, which have significant detrimental impacts on conventional crude oil processing units. The concentration of this metal in bitumen and heavy oils is generally much higher, which poses a problem for the economical upgrading of these feedstocks (Chirinos et al, 2013). These problems are relevant since the world reserves of conventional light oils are dwindling and being replaced by an increasing amount of heavier feedstocks.…”
Section: Introductionmentioning
confidence: 99%
“…12,13 Todavia, estes complexos de porfirina são importantes marcadores geoquímicos, visto que a medida da razão entre níquel e vanádio no óleo auxilia na determinação do tipo de paleoambiente deposicional no qual foi depositada a matéria orgânica que deu origem à rocha geradora e ao petróleo, podendo ser usada em correlações óleo-rocha geradora ou óleo-óleo. 14,15 As porfirinas de níquel predominam em óleos provenientes de rochas geradoras depositadas em paleoambientes mais óxidos. Entretanto, em condições redutoras, ocorre a proliferação de bactérias redutoras de sulfato, o que leva à formação de sulfeto de hidrogênio e, posteriormente, à precipitação de sulfeto de níquel, favorecendo a complexação do íon vanadil (VO 2+ ) livre com a porfirina.…”
Section: Introductionunclassified